The Pagemaster [videorecording (DVD)] - Culkin, Macaulay, 1980-; Lloyd, Christopher, 1938-; Harris, Mel, 1957-; Goldberg, Whoopi, 1955-; Stewart, Patrick, 1940-; Nimoy, Leonard (20th Century Fox Home Entertainment, 2013)
A tale of adventure and fantasy, which sends a young boy into the pages of the world's greatest stories. Seeking refuge from a storm, timid Richard Tyler enters an empty library only to be swept away into the magical animated world of The Pagemaster, where legendary characters from literary classics come alive. Guided by a trio of talking books--Adventure, Fantasy and Horror--Richard must conquer his greatest fears before he can find his way home.